Treatment of Advanced-Stage Large Cell Neuroendocrine Cancer (LCNEC) of the Lung: A Tale of Two Diseases - Atieh, Tahani; Huang, Chao H. (Frontiers in Oncology, 2021)
LCNEC of the lung comprises a small proportion of pulmonary malignancies. Traditionally, they have been classified based on histologic and immunohistochemistry characteristics with features of small cell and non-small cell lung cancer. The treatment outcome of advanced-stage LCNEC of the lung is poor with response rates ranging from 34 to 46% with platinum doublets, median progression-free survival (mPFS) ranging between 4.4 and 5.8 m, and median overall survival (mOS) ranging from 8 to 12.6 m. The optimal treatment strategy for LCNEC is debated given limited data and different outcomes based on chemotherapy type reported in the available literature. Recently, genomic profiling with Next Generation Sequencing (NGS) has been able to sub-classify LCNEC as SCLC-like or NSCLC-like. Treatment based on this sub-classification has improved outcomes by using SCLC and NSCLC regimens based on their genomic profile in retrospective analysis. Future studies in LCNEC of the lung should incorporate this new molecular sub-classification as stratification and possibly include SCLC-like LCNEC into SCLC studies and NSCLC-like into NSCLC studies.